Lost hours [large type] - Shelton, Paige (Shelton, Paige. Alaska wild series, 2024)
"A year after arriving in Benedict, Beth Rivers is feeling very at home in Alaska, even as outsiders are starting to return to enjoy the brief summer perfection. Beth feels like she's finally let go of most of her demons. She's even found her father, Eddy Rivers -- or, rather, he found her -- and she's trying to find the middle ground between anger and forgiveness. One sunny July day, Beth boards a tourist ship to see the glaciers, the main reason visitors venture to the area, and something Beth hasn't attempted until now. But when the captain has to navigate to an island, a bloodied woman is found standing on the shore, waving for help. When she's brought aboard, she claims she was kidnapped from her home in Juneau and that a bear on the island killed her captor. She, however, is unharmed. The woman, Sadie, finds a sympathetic ear in Beth. She tells her that she's been in Juneau under witness protection, and that the Juneau police don't like her. When another kidnapping occurs, Beth and police chief Gril can't help but think the two cases are interwoven, though the clues to solving them will be harder to unravel."--